Method for preventing sodium pyrosulfite from caking
By adding water-soluble anhydrous compounds to sodium metabisulfite, the agglomeration cycle is extended, the problem of sodium metabisulfite prone to agglomeration is solved, and the convenience of storage and use and production efficiency are improved.
Patent Information
- Application Number
- CN202411563615.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-03
AI Technical Summary
Sodium metabisulfite is prone to agglomeration during transportation and storage, resulting in increased costs, difficulty in use and environmental and health problems. The existing anti-caking methods have limited effects, affecting production efficiency and costs.
Add 0.01-6% water-soluble anhydrous compounds, such as anhydrous calcium chloride, anhydrous magnesium sulfate or anhydrous sodium sulfate, to sodium metabisulfate, and mix and package through a gas flow delivery pipeline to extend the agglomeration cycle.
The storage cycle of sodium metabisulfite is extended to more than six months, which significantly improves the convenience of storage and use of products, reduces the risk of agglomeration in production and transportation, and provides a better marketing environment.
Smart Images

Figure BDA0005118590980000031 
Figure BDA0005118590980000051 
Figure BDA0005118590980000061
Abstract
Description
Technical Field
[0001] The invention relates to an anti-caking method, and more specifically, to an anti-caking method for sodium pyrosulfite. Background Art
[0002] Sodium Metabisulfite (Na2S2O5), as an important inorganic chemical product, is an important chemical raw material, widely used in food processing, pharmaceutical, papermaking and sewage treatment industries. At present, the annual output of sodium metabisulfite in the world has reached two million tons, and continues to grow at a steady rate.
[0003] However, due to the physical and chemical properties of sodium metabisulfite, the product is very easy to agglomerate during transportation and storage, which has been a problem for the entire industry. After sodium metabisulfite agglomerates, it generates sodium sulfite and sulfur dioxide, which brings a very unfriendly experience to users:
[0004] (1) After agglomeration, it needs to be broken, which increases a lot of cost and difficulty in use;
[0005] (2) After agglomeration, the content of the main components decreases, the usage amount needs to be increased, and the cost of use increases;
[0006] (3) It has a strong and pungent smell of sulfur dioxide, which is not friendly to the environment and human health.
[0007] Sodium metabisulfite is the product of dehydration between acid salt sodium bisulfite molecules. Because acid salts are thermally unstable, the drying process of sodium metabisulfite mostly adopts airflow drying process; the residual moisture of the finished product after drying is about one thousandth. How to solve the problems of sodium metabisulfite agglomeration and content degradation is to improve the use value and benefits of sodium metabisulfite.
[0008] The current mainstream method to prevent sodium metabisulfite from agglomerating is:
[0009] ① Optimize the production process: strictly control the temperature and humidity of the product during the production process, reduce the product moisture and packaging temperature of sodium metabisulfite, and cut off the factors that induce agglomeration from the source.
[0010] ③Change the packaging material: The current mainstream packaging method is film woven bag + inner bag packaging, which can play a certain role in waterproofing and moisture-proofing. However, due to the influence of the capillary pores of the inner bag, sodium metabisulfite is easy to absorb moisture and agglomerate during storage. By changing the material and thickness of the inner bag, the agglomeration period can be extended.
[0011] ③ Reduce the use cycle of sodium metabisulfite: Affected by different transportation, storage and other conditions, the cycle from production to the start of agglomeration of sodium metabisulfite is 10-45 days. Reducing the production-use cycle and keeping the use time of sodium metabisulfite within its agglomeration cycle will not affect the use and benefits of metabisulfite and control agglomeration from the use aspect.
[0012] 3. The three current sodium metabisulfite anti-caking methods all have certain defects, which not only affect the improvement of production capacity, but also increase production costs, and the anti-caking effect is limited, which is not conducive to the long-term development of the industry. Therefore, finding a more permanent and effective anti-caking method is a problem that the current sodium metabisulfite production companies are eager to solve, and it is also a problem that the present invention needs to solve. Summary of the invention
[0013] The object of the present invention is to provide a method for preventing sodium metabisulfite from caking, which has simple process, simple operation and significant effect, in view of the above-mentioned deficiencies in the prior art.
[0014] The technical solution of the present invention is achieved as follows: a method for preventing sodium metabisulfite from caking, comprising the following steps:
[0015] (1) preparing sodium pyrosulfite; (2) adding a water-soluble anhydrous compound having a stronger water absorption property than sodium pyrosulfite and capable of generating a stable crystalline water compound to the sodium pyrosulfite, wherein the amount of the water-soluble anhydrous compound added accounts for 0.01-6% of the total mass of the sodium pyrosulfite; (3) mixing the sodium pyrosulfite and the water-soluble anhydrous compound uniformly and then packaging to obtain a finished product.
[0016] In the above-mentioned method for preventing sodium metabisulfite from caking, step (2) specifically comprises: the prepared sodium metabisulfite is delivered to the packaging section through an air flow conveying pipeline, a material mixing unit is arranged on the air flow conveying pipeline, an auxiliary material adding pipeline is connected to the air flow conveying pipeline on one side of the feed end of the material mixing unit, an anhydrous compound is added to the air flow conveying pipeline through the auxiliary material adding pipeline and mixed through the material mixing unit; the amount of the water-soluble anhydrous compound added is 0.01-6% of the total mass of the sodium metabisulfite.
[0017] In the above-mentioned method for preventing sodium metabisulfite from caking, the water-soluble anhydrous compound is any one of anhydrous calcium chloride, anhydrous magnesium sulfate and anhydrous sodium sulfate, or a mixture of any two or more thereof.
[0018] In the above-mentioned method for preventing sodium metabisulfite from caking, the material mixing unit is a drum screen.
[0019] In the above-mentioned method for preventing sodium metabisulfite from caking, the amount of the water-soluble anhydrous compound added is 0.02-1% of the total mass of the sodium metabisulfite.
[0020] After adopting the above scheme, the present invention has the following unexpected beneficial effects compared with the prior art by adding a water-soluble anhydrous compound that does not affect the product quality to the sodium pyrosulfite:
[0021] The product agglomeration cycle is extended to more than six months, which greatly increases the effective storage period of sodium metabisulfite. On this basis, the previous mode of sodium metabisulfite products that can only be produced in small inventories can be changed. Within the six-month period, the production-sales-use links will not be affected by the agglomeration factor of sodium metabisulfite, which is extremely convenient in all links and provides a better marketing environment for future sodium metabisulfite production companies. DETAILED DESCRIPTION
[0022] The present invention will be further described in detail below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0023] A method for preventing sodium metabisulfite from caking of the present invention comprises the following steps:
[0024] (1) Preparation of sodium metabisulfite: This is a conventional technique in the art and will not be described in detail herein. Any conventional technique in the art may be used.
[0025] (2) The prepared sodium metabisulfite is delivered to the packaging section through an air flow conveying pipeline, a drum screen is arranged on the air flow conveying pipeline, and an auxiliary material adding pipeline is connected to the air flow conveying pipeline on the feeding end side of the material mixing unit. The anhydrous compound is added to the air flow conveying pipeline through the auxiliary material adding pipeline and mixed through the drum screen; the drum screen can well stir and mix the anhydrous compound and the sodium metabisulfite while screening out the lumps in the sodium metabisulfite powder.
[0026] The amount of the water-soluble anhydrous compound added is 0.01-6% of the total mass of the sodium metabisulfite, preferably 0.02-1%; the water-soluble anhydrous compound is any one of anhydrous calcium chloride, anhydrous magnesium sulfate and anhydrous sodium sulfate or a mixture of any two or more thereof.
[0027] (3) The sodium metabisulfite and the water-soluble anhydrous compound are mixed evenly and then packaged to obtain a finished product.
[0028] Study on the Agglomeration Mechanism of Sodium Metabisulfite Products
[0029] Sodium metabisulfite products are white or slightly yellow crystalline powders. Crystalline chemical products often produce agglomeration, which makes transportation and use difficult, so it is very important to prevent agglomeration of crystal products. The main reason for the agglomeration of crystal products is the dissolution and recrystallization of the crystal surface. There are three main factors that cause this phenomenon: First, the exchange of moisture between the crystal surface and the atmosphere. When the air temperature is greater than the critical temperature of the crystal, the crystal absorbs moisture; when it is less than the critical temperature, the crystal remains dry. This causes the formation of crystal bridges between the grains and adhesion, resulting in agglomeration of crystal products. Second, the chemical reaction between the crystal surface material and the material in the atmosphere (oxygen, water vapor, etc.) causes agglomeration. Third, the capillary adsorption force between the grains causes the diffusion of water vapor; changes in the humidity gradient inside the crystal material can also cause agglomeration. There are many factors that affect the agglomeration of crystal products. The particle size, particle size distribution and crystal habit of the product are important factors. Anti-agglomeration mainly starts from these factors. There are many ways to prevent agglomeration of crystal products. According to the habits of the crystal product itself, there are mainly the following methods. ⑴ Granulation. Make the product have suitable particle size, narrow particle size distribution and good crystal habit.
[0030] ⑵ Drying: Dry the product, and package, store and transport the crystal product under extremely low humidity conditions.
[0031] ⑶ Anti-caking agent. Add additives to prevent crystal products from agglomerating, so that the product can be prevented from agglomerating while maintaining chemical stability and not affecting product quality and use effect. These include inert anti-caking agents, such as talcum powder, alumina, clay, etc.; surface active anti-caking agents, such as octadecylamine, fatty acids, sodium alkyl sulfonate, heptadeca-heptadecylamine, etc. (Quoted from "Principles and Applications of Chemical Crystallization Process" P208)
[0032] Sodium metabisulfite is the product of dehydration between sodium bisulfite molecules, and the acid salt sodium bisulfite is extremely unstable. According to the phenomenon that the main content of sodium metabisulfite decreases significantly after agglomeration and there is a serious pungent odor, it is inferred that the presence of free water in the product and the adsorption of moisture in the air cause the formation of the following reaction chain:
[0033]
[0034] Because of the presence of water, it will not decrease after the reaction, thus forming a reaction chain. As time goes by, the crystal bridges between the crystals continue to increase and grow to form agglomerates.
[0035] Determination of the method for determining the moisture content of sodium metabisulfite products
[0036] ⑴ Selection of drying equipment: Sodium metabisulfite is a strong reducing agent and is easily oxidized by oxygen in the air. Therefore, when measuring moisture for drying, you cannot choose a general rapid moisture meter, but a vacuum drying oven with a negative pressure of 0.1MPa.
[0037] ⑵ Determination of drying temperature: According to some foreign data, sodium metabisulfite is easily decomposed in a high temperature environment, and the drying temperature cannot exceed 65°C. In addition, the boiling point of water is greatly reduced in a vacuum environment, which does not affect the rapid evaporation of water. Therefore, drying at 65°C is chosen.
[0038] ⑶ Determination of drying time After many tests, experiments were carried out at 10 minutes, 20 minutes, 30 minutes, 60 minutes and 120 minutes. When the drying temperature is 65°C, it can be dried to constant weight in 30 minutes, so the drying time is determined to be 30 minutes.
[0039] Therefore, the method for determining the moisture content of sodium metabisulfite is: use a weighing bottle to accurately weigh about 10g of sodium metabisulfite sample on an analytical balance and place it in a vacuum drying oven. After vacuuming, heat it to 65°C. After keeping the temperature constant for 30 minutes, take out the sample and transfer it to a dryer to cool it to room temperature, and then weigh it accurately. The quotient of the difference in weight between the two samples and the original weight is the moisture content. The laboratory equipment involved in this detection method is an analytical balance, a vacuum drying oven, a dryer, a weighing bottle, etc.
[0040] Selection of anti-caking methods for sodium metabisulfite products
[0041] After many experiments and analyses, the three anti-caking methods introduced in "Principles and Applications of Chemical Crystallization Process" are not suitable for sodium metabisulfite.
[0042] ⑴ Granulation. Because sodium metabisulfite products have low added value and high yield, granulation requires a large amount of equipment and operating costs, resulting in an increase in production costs and making the product lose competitiveness;
[0043] ⑵ Drying. The airflow drying equipment currently used can adjust multiple parameters such as air volume and temperature, and the free moisture content in the product can basically only be stabilized at about one thousandth. In addition, there are always capillaries in the product packaging, which can slowly absorb moisture in the air and increase humidity.
[0044] ⑶ Anti-caking agent. No matter it is an inert anti-caking agent or a surfactant anti-caking agent, many experiments have been conducted, but the ideal anti-caking effect cannot be achieved; and sodium metabisulfite is a food additive, and excessive addition of inert substances and surfactants is not allowed, which will affect the quality of the product and the use effect of downstream customers.
[0045] According to the analysis of the caking mechanism of sodium metabisulfite, sodium metabisulfite is very sensitive to the presence of moisture, and the anti-caking effect can be achieved by simply cutting off the reaction chain caused by moisture; because the free moisture content in the product can basically be stabilized at about one thousandth, it is considered to add a small amount of desiccant to the product to fix the moisture on the desiccant; in addition, the thickness of the PE plastic bag inside the product packaging should be guaranteed to be 0.05mm or above and the integrity of the packaging should be guaranteed as much as possible to control the moisture absorption rate of the product.
[0046] Desiccant addition method and desiccant selection:
[0047] ⑴ Indirect addition: because sodium metabisulfite is an acidic substance, neutral or acidic desiccant can be selected and processed into small bags with breathable bags and fixed in the inner packaging bag (the weight of each small bag of desiccant is 2‰-10‰ of the finished product);
[0048] ⑵ Direct addition, that is, the desiccant and sodium metabisulfite can be directly mixed. However, the selection of desiccant must meet the following conditions:
[0049] The added desiccant must have a greater water adsorption capacity than sodium metabisulfite;
[0050] The added desiccant cannot react chemically with sodium metabisulfite;
[0051] The added desiccant cannot affect the use effect and other use requirements of downstream customers;
[0052] The added desiccant should be able to be used as a food additive;
[0053] The added desiccant cannot reduce the main content of the product to below the national standard or the customer's special requirements, so the amount added is limited.
[0054] All desiccants were screened according to the above conditions. Through multiple tests, it was found that any one of anhydrous calcium chloride, anhydrous magnesium sulfate or anhydrous sodium sulfate or any combination of them as a desiccant directly added to sodium metabisulfite had a significant effect.
[0055] Experimental Example 1
[0056] Take the finished product of sodium metabisulfite produced in the workshop and pack it in sealed bags. Weigh 500g of sodium metabisulfite and 0.05g of anhydrous calcium chloride in one bag, shake and mix thoroughly, remove the air in the bag and store it in a cool place. Weigh 500g of sodium metabisulfite in another bag, perform the same treatment and make a blank control.
[0057]
[0058]
[0059] The above experiments show that when no compounds are added, the moisture content of the product reaches about 0.2% after 60 days of storage, forming a large area of compaction; after adding anhydrous compounds, the moisture content of the product reaches about 0.2% after 150 days of storage, forming a large area of compaction.
[0060] Experimental Example 2
[0061] Take the finished product of sodium metabisulfite produced in the workshop and pack it in sealed bags. Weigh 500g of sodium metabisulfite and 0.1g of anhydrous sodium sulfate in one bag, shake and mix thoroughly, remove the air in the bag and store it in a cool place. Weigh 500g of sodium metabisulfite in another bag, perform the same treatment operation and make a control blank.
[0062]
[0063]
[0064] The above experiments show that due to the low initial moisture content of the product, when no compounds are added, the moisture content of the product reaches about 0.2% after 90 days of storage, forming a large area of compaction; after adding anhydrous compounds, the moisture content of the product reaches about 0.2% after 210 days of storage, forming a large area of compaction.
[0065] Experimental Example 3
[0066] Take the finished product of sodium metabisulfite produced in the workshop and pack it in sealed bags. Weigh 500g of sodium metabisulfite and 2g of anhydrous magnesium sulfate in one bag, shake and mix thoroughly, remove the air in the bag and store it in a cool place. Weigh 500g of sodium metabisulfite in another bag, perform the same treatment operation and make a control blank.
[0067]
[0068]
[0069] The above experiments show that due to the low initial moisture content of the product, when no compounds are added, the moisture content of the product reaches about 0.2% after 60 days of storage, i.e., a large area of compaction is formed; and after adding anhydrous compounds, the moisture content of the product is still only about 0.18% after 270 days of storage, a mixture of white solid and powder appears, and the agglomerates are fragile, and no large-scale agglomeration occurs.
[0070] Experimental Example 4
[0071] Take the finished product of sodium metabisulfite produced in the workshop and pack it in sealed bags. Weigh 500g of sodium metabisulfite, 2.5g of anhydrous magnesium sulfate and 2.5g of anhydrous sodium sulfate in one bag, shake and mix thoroughly, remove the air in the bag and store it in a cool place. Weigh 500g of sodium metabisulfite in another bag, perform the same treatment and make a blank control.
[0072]
[0073]
[0074] The above experiments show that due to the low initial moisture content of the product, when no compounds are added, the moisture content of the product reaches about 0.2% after 60 days of storage, forming a large area of compaction; after adding anhydrous compounds, the moisture content of the product is still only about 0.16% after 270 days of storage, and it still remains in powder form, but the fluidity becomes worse.
[0075] Experimental Example 5
[0076] In the sodium metabisulfite packaging production line in the workshop, 1500g of anhydrous magnesium sulfate is added to every 25kg of powder through the sampling port, and after hot-melt packaging, it is fully kneaded and mixed. Another batch of sodium metabisulfite products from the same production line is taken as a blank control.
[0077]
[0078]
[0079] The above experiments show that due to the low initial moisture content of the product, when no compounds are added, the moisture content of the product reaches about 0.21% after 60 days of storage, i.e., a large area of compaction is formed. Judging from the moisture content, a large area of compaction has been formed in more than a month; after adding anhydrous compounds, the moisture content of the product is still only about 0.17% after 270 days of storage. The product is composed of a mixture of white solid and powder, and the agglomerates are fragile.
[0080] It can be seen from the above implementation case 1.2.3 that among the anhydrous compounds, anhydrous calcium chloride, anhydrous sodium sulfate and anhydrous magnesium sulfate can all play a good anti-caking role.
[0081] From the above-mentioned Example 4, it can be seen that the anti-caking effect of mixed addition of anhydrous compounds is the same as that of a single anhydrous compound, and they can be mixed and used together.
[0082] From the above experiments, it can be seen that adding a suitable proportion of soluble anhydrous compounds to sodium metabisulfite is crucial to prevent powder agglomeration and has unexpected beneficial effects. Without affecting product quality, the shelf life of the product can be greatly extended. When the added amount reaches a certain amount, its shelf life can even exceed half a year and reach one year. This can change the common problem of short shelf life of products in the industry.
[0083] The above embodiments are preferred implementation modes of the present invention and are only used to facilitate the description of the present invention. They are not intended to limit the present invention in any form. Any person with ordinary knowledge in the relevant technical field, if they do not depart from the scope of the technical features of the present invention, can make equivalent embodiments by partial changes or modifications to the technical contents disclosed in the present invention, and they still fall within the scope of the technical features of the present invention without departing from the technical features of the present invention.
Claims
1. A method for preventing sodium metabisulfite from caking, characterized in that: The steps include: (1) preparing sodium pyrosulfite; (2) adding a water-soluble anhydrous compound having a stronger water absorption property than sodium pyrosulfite and capable of generating a stable crystalline water compound to the sodium pyrosulfite, wherein the amount of the water-soluble anhydrous compound added accounts for 0.01-6% of the total mass of the sodium pyrosulfite; (3) mixing the sodium pyrosulfite and the water-soluble anhydrous compound uniformly and then packaging to obtain a finished product.
2. A method for preventing sodium metabisulfite from caking according to claim 1, characterized in that: Step (2) specifically comprises: the prepared sodium metabisulfite is delivered to the packaging section through an air flow conveying pipeline, a material mixing unit is arranged on the air flow conveying pipeline, an auxiliary material adding pipeline is connected to the air flow conveying pipeline on one side of the feed end of the material mixing unit, an anhydrous compound is added to the air flow conveying pipeline through the auxiliary material adding pipeline and mixed through the material mixing unit; the amount of the water-soluble anhydrous compound added is 0.01-6% of the total mass of the sodium metabisulfite.
3. A method for preventing sodium metabisulfite from caking according to claim 1 or 2, characterized in that: The water-soluble anhydrous compound is any one of anhydrous calcium chloride, anhydrous magnesium sulfate and anhydrous sodium sulfate, or a mixture of any two or more thereof.
4. A method for preventing sodium metabisulfite from caking according to claim 2, characterized in that: The material mixing unit is a drum screen.
5. The method for preventing sodium metabisulfite from caking according to claim 1, characterized in that: The amount of the water-soluble anhydrous compound added is 0.02-1% of the total mass of the sodium pyrosulfite.
